Cost–Benefit and Cost–Utility Analysis of Amphotericin B Supplementation of Corneal Storage Media With Endothelial Keratoplasty-Prepared Tissue. Issue 4 (April 2020) - Chiang, Trent Tsun-Kang; Shtein, Roni M.; McCoy, Kristen; Hurlbert, Susan; Grossman, Gregory H.
Abstract : Purpose: To determine the cost-effectiveness of amphotericin B supplementation, we analyzed both current costs to treat postendothelial keratoplasty (EK) fungal infections and potential costs associated with amphotericin B supplementation. Methods: We collected 19 US cases of post-EK fungal eye infections from the published literature and assessed the associated costs from the literature. A survey of surgeons was also conducted with questions regarding their experiences in managing these infections. Results: We estimated that the costs to diagnose, manage, and treat post-EK fungal keratitis and post-EK fungal endophthalmitis are USD $21, 113 and $34, 850, respectively. The largest portion of the costs can be attributed to the need for additional surgical management, which is required in 79% of the cases. We estimated the total cost of amphotericin B supplementation to be $44.39 per graft with use of conventional amphotericin B and conservative assumptions regarding supplementation processes. Cost-effectiveness analysis demonstrated that amphotericin B supplementation is cost-effective at $100, 000 per quality-adjusted life-year level only if amphotericin B supplementation can prevent more than 69.62% of post-EK fungal infections, assuming the incidence of post-EK fungal infection remains at the level it was between 2012 and 2017. Conclusions: We found that amphotericin B supplementation can be cost-effective under conservative assumptions if it is moderately effective in preventing post-EK fungal infections.